Hyperinsulinemia promotes endothelial inflammation via increased expression and release of Angiopoietin-2. (August 2020) - Chandel, Shivam; Sathis, Anuradha; Dhar, Monalisa; Giri, Hemant; Nathan, Abel Arul; Samawar, Sai Kiran Reddy; Gupta, Akshari; Gopal, Jayashree; Harish, Ranjani; Mohan, Viswanathan; Dixit, Madhulika
Abstract: Background and aims: Angiopoietin-2 (ANG-2) mediates endothelial inflammation to initiate atherosclerosis and angiogenesis. Here we determined the serum levels of ANG-2 in hyperinsulinemic subjects and whether insulin increases its expression and release. Methods: Healthy male subjects were recruited from the D-CLIP and CURES studies and, based on their fasting insulin levels, were classified as normoinsulinemic (n = 228) and hyperinsulinemic (n = 32). Serum proteins were estimated by ELISA. Endothelial inflammation was scored as the number of THP-1 monocytes adhered to HUVEC monolayer. Gene expression was determined with promoter reporter assays and semi-quantitative RT-PCR. Western blotting was used to assess changes in protein expression and activation. Immunofluorescence imaging and ChIP assay were used for nuclear localization and promoter binding studies, respectively. Results: ANG-2 and sTIE2 levels were higher in hyperinsulinemic subjects. Hyperinsulinemic serum elicited endothelial inflammation, which was abrogated by an ANG-2 blocker antibody. Insulin (100 nM) increased mRNA and protein expression of ANG-2, and its release from HUVECs. It induced activation of p38 MAPK and an increase in protein levels and nuclear localization of cFOS. Binding of cFOS to the −640 to −494 promoter region mediated insulin dependent ANG-2 transcription. p38 MAPK inhibitor (25 μM) blocked insulin-induced nuclear localization of cFOS, expression of ANG-2 and ICAM-1, and release of ANG-2 into the culture medium. Spent medium collected from insulin treated cells enhanced endothelial inflammation, which was lost upon ANG-2 knockdown as well as upon p38 MAPK inhibition. Conclusions: ANG-2 levels are high in hyperinsulinemic subjects and insulin induces expression and release of ANG-2 from HUVECs through p38 MAPK-cFOS pathway to elicit endothelial inflammation. Graphical abstract: Image 1 Highlights: Circulating levels of Angiopoietin-2 (ANG-2) are high in hyperinsulinemic insulin resistant men. ANG-2 nullifying antibody abrogates endothelial inflammation elicited by hyperinsulinemic serum. Insulin promotes expression and release of ANG-2 from endothelial cells in a p38 MAPK dependent manner. cFOS transcription factor activates transcription by binding to c-FOS site present between −640 and −494 of ANG-2 promoter.